MYC proteins promote neuronal differentiation by controlling the mode of progenitor cell division. (5th March 2014) - Zinin, Nikolay; Adameyko, Igor; Wilhelm, Margareta; Fritz, Nicolas; Uhlén, Per; Ernfors, Patrik; Henriksson, Marie Arsenian
Synopsis <boxed-text content-type="graphic" id="embr201337424-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> This study reveals an unexpected role for MYC in the control of stemness versus differentiation of neural stem cells in vivo and shows that Myc represses Notch signaling and promotes asymmetric neurogenic cell divisions. Elevated MYC levels increase neurogenesis in the developing chick neural tube The neurogenic function of MYC depends on the integrity of the polarized neural tissue MYC promotes apico‐basal neurogenic divisions